PERBANDINGAN JENIS PAKAN DAN SISTEM PEMELIHARAAN TERNAK BABI PADA PETERNAK DI KOTA AMBON - Evarina Sarioa; Christian W. Patty; Jomima M. Tatipikalawan (MARSEGU : Jurnal Sains dan Teknologi, 2025)
This study aims to analyze the comparison of feed types and rearing systems on the production performance of pigs raised by farmers in Ambon City. Pig farming has significant economic and socio-cultural value in this region, serving as both a source of animal protein and an integral part of local traditions. The research method used was a survey with data collected through interviews and direct observations of pig farmers across several areas in Ambon City. The observed variables included feed types, rearing systems (intensive and semi-intensive), and production performance indicators such as weight gain, feed efficiency, and survival rate. The results showed that both feed types and rearing systems significantly affected pig performance. Intensive farming systems using locally mixed fermented feed produced better growth outcomes compared to traditional systems using household food waste. Increasing farmers’ knowledge about feed management and rearing practices is essential to improve productivity and promote a more efficient and sustainable pig farming system in Ambon City.